Executive-interpretive analysis of the sonata for plane no. 1, op. 22, by Alberto Ginastera (2017)
This article aims to offer analytical tools about various aspects that are useful to professional or training pianists, for the study and execution of the piano sonata No. 1, op.22, by the Argentine composer Alberto Ginastera. A short historical context of the work is included, with special focus on the creative period of which it is a part, in order to familiarize the pianist with the composer's production. The article also has an analysis of the structure of the work and each of its movements and practical advice focused on the executive-interpretive technical aspect, whose purpose is to facilitate both the study and the execution of the work itself. It also includes a brief analysis of three recordings of the sonata with general comments related to the specific issues addressed in the article.